2015
DOI: 10.1371/journal.pone.0131525
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Improves Amyloid β-Peptide (1-42) Induced Spatial Memory Deficits through BDNF-ERK Signaling Pathway

Abstract: Curcumin, the most active component of turmeric, has various beneficial properties, such as antioxidant, anti-inflammatory, and antitumor effects. Previous studies have suggested that curcumin reduces the levels of amyloid and oxidized proteins and prevents memory deficits and thus is beneficial to patients with Alzheimer’s disease (AD). However, the molecular mechanisms underlying curcumin’s effect on cognitive functions are not well-understood. In the present study, we examined the working memory and spatial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
78
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(95 citation statements)
references
References 48 publications
8
78
1
2
Order By: Relevance
“…Thus, the absence of BDNF action might be responsible for AD symptoms, including neuronal dysfunctions. 10,29,30) Previous reports have shown that a direct 31) or indirect 32) increase of BDNF levels reduces ADlike symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the absence of BDNF action might be responsible for AD symptoms, including neuronal dysfunctions. 10,29,30) Previous reports have shown that a direct 31) or indirect 32) increase of BDNF levels reduces ADlike symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…A combination of adaptogens, Eleutherococcus senticocus, Schisandra chinensis, and Rhodiola rosea, raises HSP levels (Panossian et al 2009) and improves memory and cognitive performance (Aslanyan et al 2010). Curcumin activates HSF1 (Teiten et al 2009) and augments memory function (Zhang et al 2015a). Capsaicin activates calcium channels (TRPV) and thereby activates HSF1 (Bromberg et al 2013) and improves cognitive function while blocking tau phosphorylation and β-amyloid accumulation in a diabetic-dementia animal model (Yang et al 2015).…”
Section: Hsf1 Inducers and Cognitive Preservationmentioning
confidence: 99%
“…[8,10] Accordingly, Nam et al [9] reported that the protective effect of curcumin is mediated by the prevention of oxidative stress leading to apoptosis. Curcumin as an antioxidant primarily protects biomembranes against peroxidative damage, a free-radical-mediated chain reaction, damaging cell membranes.…”
Section: Discussionmentioning
confidence: 99%
“…[4] Curcumin's preventative and protective roles on learning and memory is related to apoptotic effect, as it impairs the consolidation of memory and reverses cognitive alterations, by inhibiting programmed cell death. [8,10] Accordingly, Nam et al [9] reported that the protective effect of curcumin is mediated by the prevention of oxidative stress leading to apoptosis. Curcumin as an antioxidant primarily protects biomembranes against peroxidative damage, a free-radical-mediated chain reaction, damaging cell membranes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation